Zeolitic rock as a new pigment for ceiling paints : Influence of the pigment volume concentration - Del Amo, Delia Beatriz (2005)
The performance of a zeolitic rock, mainlyclinoptilolitic (heated at 350 C) is studied as humidityand ammonia adsorber in ceiling paints. The paints were formulated with 39% and 75% of zeolitic rock byvolume of the total pigment content and 75% and 85% pigment volume concentration (PVC). A blank, without zeolitic rock, was also formulated. The performance of the paints were assessed bygas (water and ammonia) adsorption and adsorption–desorption cycled tests. The results show that the paints containing zeolitic rock have better performance than the blank. Moreover, paints with 75% PVC behaved better than paints with PVC 85%. This behaviour maybe due to the higher pigment content because the paints with PVC 85% retain more water during the curing period diminishing their adsorption capacity.